2018
DOI: 10.1088/1475-7516/2018/03/043
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the mass of dark photons and axion-like particles through black-hole superradiance

Abstract: Ultralight bosons and axion-like particles appear naturally in different scenarios and could solve some long-standing puzzles. Their detection is challenging, and all direct methods hinge on unknown couplings to the Standard Model of particle physics. However, the universal coupling to gravity provides model-independent signatures for these fields. We explore here the superradiant instability of spinning black holes triggered in the presence of such fields. The instability taps angular momentum from and limits… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
230
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 237 publications
(240 citation statements)
references
References 88 publications
7
230
3
Order By: Relevance
“…The critical mass mM above which the instability ceases to exist decreases when J/M 2 decreases. These behaviours for the superradiant instability of massive Proca fields are similar to those found in massive scalars in the Kerr black hole, as pointed out in [10,31,33]. The plots in the lower panel of Fig.…”
Section: Kerr: Unstable Modes At Fixed Black Hole Rotationsupporting
confidence: 81%
See 2 more Smart Citations
“…The critical mass mM above which the instability ceases to exist decreases when J/M 2 decreases. These behaviours for the superradiant instability of massive Proca fields are similar to those found in massive scalars in the Kerr black hole, as pointed out in [10,31,33]. The plots in the lower panel of Fig.…”
Section: Kerr: Unstable Modes At Fixed Black Hole Rotationsupporting
confidence: 81%
“…Although direct detection of dark matter proves to be very difficult, recently a new line of investigation has opened up with a flurry of papers considering the interplay of these ultralight bosons and superradiance from black holes [7][8][9][10][11][12]. In particular, it has been shown that the instabilities from these superradiant modes can, in principle, be used to detect beyond Standard Model particles [7] and put bounds on the potential masses of dark matter candidates, e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For it to sit at the critical tide, M µ ∼ 2 × 10 −3 . The timescale τ for growth of clouds via superradiance is of order τ ∼ (M µ) −9 M [6], too large to be meaningful for scalar fields, but potentially affecting vectors (τ ∼ (M µ) −7 M ) [33,36,37]. The tide is also small enough that it should not be affecting any of the constraints derived from the possible non-observation of GWs from the system [38,39].…”
Section: Application To Astrophysical Systemsmentioning
confidence: 99%
“…First of all, we mean the non-minimal extensions of the axion models, which are based on the F (R) modifications of the theory of gravity (see, e.g., [17][18][19][20][21]), on the non-minimal extensions of the theory of the axion-photon coupling [22], and on the axionically extended models of the dynamic aether [23]. The second trend is associated with the recent surge of interest to the black hole mergers and supermassive black holes: the axionic dark matter can play the role of * Electronic address: Alexander.Balakin@kpfu.ru † Electronic address: groshevdmitri@mail.ru a marker revealing specific features of the strong gravitational field (see, e.g., [24,25] as illustrations). The third trend is connected with the modeling of axionic structures of different scales, associated with the galactic halos, miniclusters, halos surrounding the magnetars, dyons, etc.…”
Section: Introductionmentioning
confidence: 99%